2018
DOI: 10.1097/md.0000000000012302
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-2 gene polymorphisms are associated with ischemic stroke in a Hainan population

Abstract: Ischemic stroke is a complex vascular disease, which has become 1 of the major causes of morbidity and mortality worldwide. More and more data showed that matrix metalloproteinases (MMPs), in particular, MMP-2 are deleterious after ischaemic stroke. This study investigated the relationship between MMP-2 and stroke risk in the Southern Chinese population.We evaluated single nucleotide polymorphisms (SNP) of MMP-2 in stroke patients in an association study using a case-control design. Six SNPs of MMP2 were selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Manso et al 23 reported that MMP2 gene polymorphisms are associated with the outcome of ischemic stroke after 3 months; however, other studies have failed to show a significant association between MMP2 1306C/T and 735C/T sites and carotid intima-media thickness. 24 Liu et al demonstrated that the 735C/T polymorphism of MMP2 is associated with ischemic stroke in a Chinese population. 25 Additionally, Xu et al reported that the 1306C/T polymorphism of MMP2 is associated with atherosclerotic cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Manso et al 23 reported that MMP2 gene polymorphisms are associated with the outcome of ischemic stroke after 3 months; however, other studies have failed to show a significant association between MMP2 1306C/T and 735C/T sites and carotid intima-media thickness. 24 Liu et al demonstrated that the 735C/T polymorphism of MMP2 is associated with ischemic stroke in a Chinese population. 25 Additionally, Xu et al reported that the 1306C/T polymorphism of MMP2 is associated with atherosclerotic cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of MMP gene variations in various diseases with acute brain damage have been investigated. A significant relationship was found between the genetic variations identified in MMP genes and changes in MMP enzyme expression levels [7,17]. MMPs have been associated with various physiological and pathological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation promotes atherosclerotic plaque formation and plaque rupture, and thus can lead to the development of ischemic stroke (6). Clinical, environmental, and demographic risk factors have been associated with the development and pathogenesis of ischemic stroke [7]. In addition, ischemic stroke is accepted as a multifactorial disease in which genetic and environmental factors play together a role in its pathogenesis [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…more specifically, ectopic vascular calcification has become an important topic in public health and over the last years, several studies have shown the important involvement of MMPs and TIMPs in cardiovascular diseases, including coronary artery disease, 107 myocardial infarction, 108 atherosclerosis, 109 and ischemic stroke. 110,111 In cardiovascular diseases, MMPs act in the weakening of vessels since they are able to degrade all their major components, essential for the maintenance of vascular tonus. 112 The main MMPs involved in cardiovascular diseases are MMP-2 and MMP-9.…”
Section: Mmps and Ectopic Vascular Calcificationmentioning
confidence: 99%